2016
DOI: 10.1103/physrevb.93.104520
|View full text |Cite
|
Sign up to set email alerts
|

Nodal superconducting gap in tetragonal FeS

Abstract: Low temperature specific heat has been measured in superconductor β-FeS with Tc = 4.55 K. It is found that the low temperature electronic specific heat Ce/T can be fitted to a linear relation in the low temperature region, but fails to be described by an exponential relation as expected by an s-wave gap. We try fittings to the data with different gap structures and find that a model with one or two nodal gaps can fit the data. Under a magnetic field, the field induced specific heat coefficient ∆γe=[Ce(H)-Ce(0)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 38 publications
8
43
1
Order By: Relevance
“…However, the incoherent spectral weight of γ might still contribute to the zero-energy excitations at low temperatures. This could explain the nodal-gap-like behavior observed in thermal conductivity and specific heat measurements [20,21]. On the other hand, because the incoherent γ band would not contribute to the superfluid response, if the superconducting gaps in the other bands are nodeless, µSR could still observe an overall nodeless-gap behavior for FeS [18,19].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the incoherent spectral weight of γ might still contribute to the zero-energy excitations at low temperatures. This could explain the nodal-gap-like behavior observed in thermal conductivity and specific heat measurements [20,21]. On the other hand, because the incoherent γ band would not contribute to the superfluid response, if the superconducting gaps in the other bands are nodeless, µSR could still observe an overall nodeless-gap behavior for FeS [18,19].…”
Section: Discussionmentioning
confidence: 94%
“…Muon spin rotation (µSR) measurements favor the fully-gapped superconductivity coexisting with a low-moment magnetic state at low temperature in polycrystalline FeS [18,19]. On the contrary, thermal conductivity and specific heat measurements support the existence of a nodal gap [20,21], while scanning tunneling spectroscopy indicates a highly anisotropic or nodal superconducting gap structure [22]. Furthermore, a theoretical calculation predicted d x 2 −y 2 pairing symmetry in FeS [23].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the right-hand side of the relation, we use the Sommerfeld coefficient of γ = 5.73 mJ/(mol K 2 ) [34] and T c = 9.1 K for FeSe [20]. For FeS, γ = 3.8 mJ/(mol K 2 ) [6]. Because T c for FeSe was determined with a zero-resistance criterion in [20], we use a similarly determined T c of 3.9 K for FeS for the comparison.…”
Section: Methodsmentioning
confidence: 99%
“…This conclusion contrasts with some other studies of tFeS, which have found evidence for nodes in the gap function. 30,31 However, a previous µSR study has also reported fully-gapped behaviour, though the best fit was for two s-wave gaps.…”
mentioning
confidence: 93%